Nuptial feeding in the freshwater snail Pomacea canaliculata (Gastropoda: Ampullariidae) - Burela, Silvana (2007)
The males of the freshwater snail Pomacea canaliculata have a copulatory apparatus consisting in a delicate penis running through a muscular channeled sheath bearing three different glands. The outer gland is the most conspicuous one and often secrets a sticky drop of mucus during copula. However, its function is enigmatic because it opens toward the exterior of the palliai cavity. During laboratory trials performed to register copula duration and mating behaviour, we observed that females of P canaliculata eat this secretion with approximately two deglutition events on average during the copula. This behaviour can be interpreted as a nuptial feeding, possibly functioning as an additional male mating effort to entice the female to remain in copula for long periods. To our best knowledge, there are no previously registered cases of nuptial feeding in gastropods.